A Good Childhood : searching for values in a competitive age - Layard, P. R. G. (P. Richard G.); Dunn, Judy, 1939-; Good Childhood Inquiry (London : Penguin Books, 2009)
This book, which is a result of a two year investigation by the Children's Society and draws upon the work of the UK's leading experts in many fields, explores the main stresses and influences to which every child is exposed including family, friends, youth culture, values, and schooling.
Includes bibliographical references (p. 208-226) and index.
Keywords: Children -- Great Britain -- Social conditions -- 21st century; Poor children -- Great Britain -- Social conditions -- 21st century; Poor children -- Cross-cultural studies; Child rearing -- Great Britain -- 21st century; Child development -- Research -- Great Britain